Project Based Mandarin Learning with Emphasis on Chinese Cultural Appreciation at Mandarin Education Study in Makassar - Mir'ah Azizah (Civiliza Publishing, Indonesia., 2025)
In many educational settings particularly in vocational schools Mandarin instruction still focuses heavily on grammar drills and vocabulary memorization, while the development of cultural understanding often receives less attention. This study aims to explore the implementation of Project-Based Learning (PBL) in Mandarin language education with a specific focus on Chinese cultural appreciation. Using a qualitative descriptive approach, data were collected through observation, questionnaires, and project evaluations. The results show that the application of PBL significantly increased students’ engagement, creativity, and confidence in using Mandarin in real-life contexts. Moreover, students demonstrated a deeper appreciation of Chinese traditions, values, and aesthetics, which fostered their cross-cultural awareness and multicultural competence. In conclusion, Project-Based Mandarin Learning with an emphasis on cultural appreciation proves to be an effective pedagogical strategy to link language learning with cultural understanding. This approach supports the development of communicative, cognitive, and cultural skills that are relevant to global education and the 21st-century learning framework.